The role of occupational health surveillance for preventing COVID-19 infection at workplace: a review of Italian emergency legislation from March 2020 to March 2021 - Francesco CHIRICO; Angelo SACCO; Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
Occupational health surveillance is crucial to tackle the spread of COVID-19 infection at wor- kplace. Aim of this paper is to review the Italian regulations concerning the role of occupational health surveillance and released by lawmakers during the COVID-19 emergency, from March 2020 to March 2021. Occupational physician plays a major role as a “global” consultant of em- ployers to organize all the measures needed to reduce contact and to prevent COVID-19 infection and transmission. More specifically, the occupational physician has to support employers for the SARS-CoV-2 risk assessment, including the activities of information and formation for workers, in order to fight disinformation and fake news. According to the Italian Ministry of Health, priority should be given by occupational physicians to medical examinations for the so-called “fragile”wor- kers (i.e. those affected by immunosuppression or from oncological pathologies, or diseases with connotation of gravity) to minimize their risk of contracting the COVID-19 infection. Moreover, occupational physicians should check COVID-19 survivors before their returning to work. In the framework of workplace health promotion programs, occupational physicians may employ serolo- gical tests for epidemiological surveys, whereas “rapid” swabs could be useful to screen employees for suspected COVID-19 infection. Finally, when a worker becomes ill, occupational physicians are called to collaborate with Departments of Local Health Unit for the contact tracing activity.